Geographical distribution of Boeckella and Neoboeckella (Calanoida: Centropagidae) in Peru - Samanez, Iris (2014)
In samples of plankton collected from different localities along the Peruvian Andes, we found seven species of Boeckella (gracilis, gracilipes, calcaris, poopoensis, occidentalis, titicacae and palustris) and two of Neoboeckella (kinzeli and loffleri). All species, except Neoboeckella species were found in the Titicaca basin. In addition, B. palustris, B. gracilipes and B. calcaris were found in Moquegua, Apurimac and Pasco (south and central Andes). Boeckella titicacae appears to be restricted to the Titicaca Lake basin. Boeckella poopoensis occurs in saline water bodies with elevated conductivity and was found only at Salinas Lake in Arequipa. Boeckella occidentalis is a widespread species all along the Andes, from South in Puno to North in Cajamarca department and Neoboeckella loffleri is a new record for Peru. All samples are deposited in the Plankton Collection of the Limnology Department of the Museo de Historia Natural, Universidad Nacional Mayor de San Marcos, Lima, Peru.